Systematic review and network meta-analysis of efficacy and safety of interventions for preventing anti-tuberculosis drug induced liver injury - Pattaraporn Akkahadsee; Ratree Sawangjit; Panumart Phumart; Nathorn Chaiyakunapruk; Duangkamon Sakloetsakun (Scientific Reports, 2023)
Abstract Anti-tuberculosis drug induced liver injury (Anti-TB DILI) is the most common adverse events (AEs) necessitating therapy interruption but there is no preventing regimen. This study aimed to examine the efficacy and safety of herbs/alternative medicines for preventing anti-TB DILI. Relevant articles were identified through a systematic search in 5 international databases from inception till March 2022. All randomized controlled trials (RCT) assessing the effects of herbal or alternative medicines against anti-TB DILI were included. The network meta-analysis (NMA) was used to synthesize the evidence for preventing hepatotoxicity using a random-effects model. A total of 3423 patients from 14 RCTs were included. The NMA indicated that supplementation of Turmeric plus Tinospora cordifolia (RR 0.07; 95% CI 0.02 to 0.28), and N-acetyl cysteine (NAC) (RR 0.09; 95% CI 0.01 to 0.75) significantly reduced the incidence of anti-TB DILI compared with placebo. In addition, poly herbal product significantly reduced alkaline phosphatase (ALP) (MD − 21.80; 95% CI − 33.80 to − 9.80) and total bilirubin (Tbil) compared with placebo (MD − 0.51; 95% CI − 0.76 to − 0.26). There was no statistically significant difference in the occurrence of AEs in any intervention. In conclusion, Turmeric plus Tinospora cordifolia, NAC and poly-herbal product may provide benefit for preventing anti-TB DILI in TB patients. However, these findings are based on a small number of studies. Additional studies are warranted to confirm the findings.